Racismo ambiental na pessoa com deficiência em situação de vulnerabilidade no centro-sul do estado de Sergipe - Oliveira, Juliana Maria Freitas de (2022)
Throughout the historical development of societies, racism emerged as a form of domination and social exclusion of groups over others. Among the aspects of racism, the term environmental racism refers to a greater burden of environmental damage directed toward poor and peripheral communities. In this scope, vulnerability can be understood as a set of individual weaknesses and social precariousness that affect a person. Among those who are in a condition of vulnerability, we can highlight People with Disabilities (PwD) who, due to various barriers, are unable to actively participate in everyday life. According to the World Health Organization (WHO), more than one billion people around the world live with some form of disability, among which about 200 million experience considerable functional difficulties. Data from the 2010 Demographic Census carried out by the Brazilian Institute of Geography and Statistics (IBGE) show that 23.9% of the Brazilian population declared that they had at least a deficiency investigated, with the highest rate of respondents being among those who defined themselves as black and yellow, both with 27%; and 65.9% have an income between 0 and 1 minimum wage. PwD have been victims of ableism, which refers to the way society discriminates against them, exposing these individuals to a marginalized position. In this context, it is observed that in Brazil, environmental racism goes beyond racial prejudice, imposing a condition of social and economic exclusion on vulnerable populations. Therefore, this research analyzes the socioenvironmental impacts of environmental racism in the daily routine of vulnerable PwD in the Center-South of the State of Sergipe, more specifically thosewho live in the communities of Santo Antônio and Colônia Treze, which are located on the outskirts of landfills in the municipality of Lagarto. Note that the aforementioned municipality has a high rate of PwD, reaching 30% of the total population, surpassing the averages of the Northeast Region (26.6%) and Brazil (23.9%). This study is a cross-sectional and exploratory-descriptive with a qualitative and quantitative approach. For the systematization of the proposal, the following steps were carried out: (1) Analysis of the situation of PwD – training of Community Health Agents (ACS) and survey of the Family Register via the Citizen's Electronic Medical Record System – SISPEC; (2) Home visits indicated by the ACS, and information from SISPEC for application of the semi-structured forms based on International Classification of Functioning, Disability and Health (ICF) qualifers by the responsible researcher; (3) Photographic records of the infrastructure of the study region. Of the 71 families registered as residents on the outskirts of landfills, 22 PwD were evaluated. The use of topics from the ICF Checklist in the research form proved to be of great value to analyze the correlation between the functionality of the interviewees and the influence of environmental factors in their routines. The data collected pointed to the difficulty of access for PwD who live in a situation of vulnerability concerning access to health, education, transport, work, leisure, which are exacerbated by deficientinfrastructure conditions. As a Technical Product generated by the research, the "Training for Community Health Agents (ACS)" was developed, which aims to train ACS to demystify and identify PwD, with a view to mitigating stigmas, in observing the accessibility of environments school and work, detection of attitudinal, structural and social barriers, selfcare activities, class activities and service relationship.